Effect of dietary fluted pumpkin (Telfairia occidentalis) extract on growth performance, body composition and haematological parameters of Nile tilapia (Oreochromis niloticus Linnaeus) - Adekunle Ayokanmi Dada; Anike Dolapo Abiodun (Journal of Fisheries, 2014)
The effect of dietary fluted pumpkin extract on growth, body composition and haematological profile was investigated in Nile tilapia Oreochromis niloticus. Fingerlings of about 5.23-5.44 g were fed diets supplemented with four concentrations ((2.5, 5.0, 7.5 and 10.0 gkg−1) of fluted pumpkin extract powder for eight weeks. Fish fed supplemented diets showed significantly improved growth performance and feed utilization over the control (0 gkg−1 fluted pumpkin extract powder) treatment. The highest specific growth rate (0.79±0.10% per day) and best food conversion ratio (0.98±0.14) were obtained in fish fed 2.5 gkg−1 fluted pumpkin extract powder diet. No differences occurred in fish carcass moisture, protein or crude lipid content among the treatments (p>0.05). Similarly no differences occurred in white blood cells among the treatments (p>0.05) but there were greater improvement in the white blood cells of fish fed on dietary fluted pumpkin extract powder compared to the fish fed the control diet. The results suggest that dietary supplementation with fluted pumpkin extract powder improved growth rate, feed utilization, white blood cells and survival of Nile tilapia O. niloticus fingerlings.